Penerapan Case Base Reasoning Pada Sistem Pakar Aspek Perkembangan Berdasarkan Standar Tingkat Pencapaian Perkembangan Anak - Nazwa Wanda Tazkiya; Wahyu Tisno Atmojo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Every child will develop in every aspect of development. But every child will experience different development in every aspect of their development. Many parents are less aware of the importance of early childhood development and pay less attention to child development in every aspect of development. The importance of aspects of child development at the age of 5-6 years where this age will be a provision for children in entering the next level such as elementary school. Efforts to overcome this problem with the development of expert systems become effective solutions. The expert system helps parents to make it easier to determine the more dominant aspects of development in children aged 5-6 years. In this expert system research, applying the Case Base Reasoning method is used to match new cases with previous cases that have been solved stored in the case base. Thus, it is expected that parents' awareness and attention to child development will increase so that parents can provide support and learning that is more optimal and in accordance with children's needs. Results obtained for more dominant aspects in the development of children aged 5-6 years based on indicators Standar Tingkat Pencapaian Perkembangan Anak (STPPA) RA which has been determined by the Decree of the Director General of Islamic Education No. 3331 of 2021 with 6 aspects of child development such as religious and moral values, physical motor, cognitive, language, social-emotional and art, test results were obtained using the case base reasoning method against expert analysis with 5 test data getting 4 accurate test data and 1 inaccurate test data so as to get an accuracy of 80%.